Respuesta :
Answer:
d. (y+25) (y-6)
Step-by-step explanation:
y²+19y-150
= y²+25y-6y-150
= y(y+25) -6(y+25)
= (y-6) (y+25)
Mark as brainliest
Answer:
(d)
Step-by-step explanation:
given
y² + 19y - 150
To factorise
Consider the factors of the constant term (- 150) which sum to give the coefficient of the y- term (+ 19)
The factors are - 6 and + 25 , since
- 6 × + 25 = - 150 and - 6 + 25 = + 19
use these factors to split the y- term
y² - 6y + 25y - 150 ( factor the first/second and third/fourth terms )
= y(y - 6) + 25(y - 6) ← factor out (y - 6) from each term
= (y - 6)(y + 25)
= (y + 25)(y - 6) ← (d)